2022
DOI: 10.3389/fpsyg.2022.948516
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-person changes in work practice and experiences due to COVID-19: Lessons learned from employees working from home, hybrid working, and working at the office

Abstract: IntroductionIn response to the requirement of keeping social distance during the COVID-19 outbreak a lot of employees needed to change from a regular office to a home-office at short notice. The aim of the present study is to explore these employees' experiences and evaluate changes in their work situation during the pandemic.MethodA mixed-method design was used with panel data collected twice in an insurance company in Norway. The first dataset was collected in December 2020 (Time 1; N = 558), with a follow u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…The most needed skills and conditions to work from home productively stated by survey employees included time management skills and communication skills, on the one hand, and quality communication channels and regular social interactions, on the other hand. These perceived skills and conditions related to WFH are confirmed by other research studies which demonstrate their positive and negative effects on the productivity of homeworkers (compare Innstrand et al, 2022;Korican Lajtman, 2023;Seinsche et al, 2023).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The most needed skills and conditions to work from home productively stated by survey employees included time management skills and communication skills, on the one hand, and quality communication channels and regular social interactions, on the other hand. These perceived skills and conditions related to WFH are confirmed by other research studies which demonstrate their positive and negative effects on the productivity of homeworkers (compare Innstrand et al, 2022;Korican Lajtman, 2023;Seinsche et al, 2023).…”
Section: Discussionsupporting
confidence: 77%
“…These findings indicated that the productivity of homeworkers may be potentially challenged by family matters, including child care. Innstrand et al (2022) surveyed employees of one insurance company in Norway to learn about their experience with WFH during the COVID-19 pandemic. They used two samples of responses collected in December 2020 (N = 558) and March 2021 (N = 601).…”
Section: Literature Reviewmentioning
confidence: 99%